Regional variability in the atmospheric nitrogen deposition signal and its transfer to the sediment record in Greenland lakes. (17th July 2018) - Anderson, N. J.; Curtis, C. J.; Whiteford, E. J.; Jones, V. J.; McGowan, S.; Simpson, G. L.; Kaiser, J.
Abstract: Disruption of the nitrogen cycle is a major component of global environmental change. δ 15 N in lake sediments is increasingly used as a measure of reactive nitrogen input but problematically, the characteristic depleted δ 15 N signal is not recorded at all sites. We used a regionally replicated sampling strategy along a precipitation and N‐deposition gradient in SW Greenland to assess the factors determining the strength of δ 15 N signal in lake sediment cores. Analyses of snowpack N and δ 15 N‐NO3 and water chemistry were coupled with bulk sediment δ 15 N. Study sites cover a gradient of snowpack δ 15 N (ice sheet: −6‰; coast − 10‰), atmospheric N deposition (ice sheet margin: ∼ 0.2 kg ha −1 yr −1 ; coast: 0.4 kg ha −1 yr −1 ) and limnology. Three 210 Pb‐dated sediment cores from coastal lakes showed a decline in δ 15 N of ca. − 1‰ from ∼ 1860, reflecting the strongly depleted δ 15 N of snowpack N, lower in‐lake total N (TN) concentration (∼ 300 μ g N L −1 ) and a higher TN‐load. Coastal lakes have 3.7–7.1× more snowpack input of nitrate than inland sites, while for total deposition the values are 1.7–3.6× greater for lake and whole catchment deposition. At inland sites and lakes close to the ice‐sheet margin, a lower atmospheric N deposition rate and larger in‐lake TN pool resulted in greater reliance on N‐fixation and recycling (mean sediment δ 15 N is 0.5–2.5‰ in most inland lakes; n  = 6). The primary control of the transfer of the atmospheric δ 15 N deposition signal to lake sediments is the magnitude of external N inputs relative to the in‐lake N‐pool.